Estilos de aprendizaje y el rendimiento académico en matemáticas en los estudiantes de la Unidad Educativa Tomas Oleas, periodo 2021-2022 - Miranda Chacaguasay, Ángel Rodrigo (2022)
Academic performance in mathematics is one of the problems faced by educational institutions worldwide since teachers unknown their students' characteristics, limiting the teaching-learning process; consequently, it affects knowledge acquisition. One of these characteristics is learning styles. The current research aims to determine the relationship between learning styles and academic performance in mathematics of students at Unidad Educativa "Tomas Oleas" academic period 2021-2022. The methodology used for this research is quantitative approach and non-experimental design. The type of research is field and cross-sectional, and the level of research is correlational. The population comprises the students from Unidad Educativa “Tomas Oleas” for the academic period 2021-2022. For the sample, a non-probabilistic-intentional sampling comprised 83 students from the 1st, 2nd and 3rd year of high school shown in table Nº4. Two learning styles tests were applied to collect the data, one by Kolb and the other by Vark, each with its four learning styles, according to Kolb Adaptive, Assimilative, Convergent, and Divergent, which consists of 12 questions. According to Vark, the Auditory, Kinesthetic, Reflective, and Visual consists of 16 questions. In addition, two hypotheses were proposed to corroborate whether there are significant differences in academic performance between Kolb's and Vark's learning styles, concluding that academic performance is related to learning styles, specifically with Kolb's, where the Assimilators are those who achieve the best academic performance, this was demonstrated by an ANOVA test where the p-value is 0. 0455. The researcher recommended that the competent entities to conduct training on Learning Styles. Moreover, it is recommended to use activities in classes such as text analysis and class participation as they are activities associated with the learning style with better academic performance.